Income-Contingent Loans: Not a Miracle Solution - de Gayardon, Ariane (International Higher Education, 2018)
With the rising costs of higher education, an increasing share of which is borne by students and their families, governments have had to design student loans schemes to open higher education to all. A popular option among economists is income-contingent loans, where repayment is calculated as a share of the borrower’s income to avoid high repayment burden. However, the three flagship countries for income-contingent loans—Australia, England, and New Zealand—are all currently experiencing financing issues. This raises the question of defining the correct specification of income-contingent loans schemes, as well as finding the proper balance between different financial aid policies.